Exploring the information seeking behaviour of university students in Singapore : perceived self-efficacy, exhibited competency and complexity of search strategies in the retrieval of information - Wong, James Hong Kang (Nanyang Technological University, 2020)
The catalyst for this study was borne out of a real-life information void on how university students in Singapore search for research information. The concept of information seeking behaviour (ISB) has been a well-studied subject by researchers over the past few decades. However, most ISB studies have been mainly focused on the informational needs of individuals and the actions taken by them to fulfil those needs. Most existing studies on ISB have been focused on university students in North America and Western Europe with few English-language researches conducted with tertiary students in Southeast Asia. In addition, many of the highly cited research on ISB were done at the turn of the millennium and may no longer apply to present day search systems due to rapid advances in search algorithms and an increasing emphasis on mobile-enabled navigation. This is exacerbated by a paradigm shift in how people from different age group interact with search systems due to changes in how user interfaces are now designed, as well as their personal history in interacting with search systems and mobile applications. This study seeks to address existing research gaps by examining factors related to ISB: (1) the information retrieval strategy used by Singapore university students; (2) the relationship between complexity of information retrieval strategy and proficiency in retrieving research information; (3) the role perceived self-efficacy plays in information retrieval competency; (4) the exhibited competency in information retrieval when using commercial search engines and library search systems such as web-scale discovery system; and (5) the roles that library orientation workshops and information literacy training play in ISB. A total of 30 Singapore university students at the bachelor’s, master’s and PhD level were recruited as the sample for this study. Semi-structured interviews that contained nine information retrieval tasks were used to construct a clearer picture of how university students in Singapore retrieve information for their day-to-day and research information needs. In particular, the study takes an in-depth look at how these students navigate commercial search engines and library search systems and whether these exhibited competencies align with their perceived self-efficacy to do so. The findings of this study revealed that the perceived self-efficacy of students was not associated with their exhibited competency to retrieve needed information. Due to its comparative ease of use, Google was relied heavily upon by students for their information needs. However, library search systems were considered to be a more reliable source for their research needs. The complexity of information retrieval strategy was also found to be positively associated with the proficiency to retrieve information. Students who implemented more complex search strategies were also observed to display greater proficiency when retrieving information. The study also found that students who had attended library information literacy training did not use of library search systems with greater frequency. This study contributes to a more comprehensive understanding of how Singapore university students retrieve information. Findings from this study can provide useful design insights for libraries that are adopting new library search systems. Instructional librarians may likewise find new areas to improve on when developing the curriculum for information literacy programmes. Ideally, this study will have a contribution to related future researches, specifically those that analyse students' thought processes and rationale as they create information retrieval strategies.